Etiology and Clinical Impact of Interictal Periodic Discharges on the Routine Outpatient Scalp EEG. Issue 3 (May 2021) - Carneiro, Fábio; Bentes, Carla; Peralta, Ana Rita
Abstract : Purpose: Periodic discharges (PDs) are common in acute structural or metabolic brain lesions, but their occurrence during follow-up of epileptic patients in an outpatient setting is rare. Aim of this article was to study whether PDs on the routine outpatient scalp EEG of patients with epilepsy, as compared with nonperiodic epileptiform discharges, are associated with drug refractoriness and the decompensation of epilepsy and particular etiologies. Methods: A retrospective case–control study. EEG reports were screened for PDs and their variants. The inclusion criteria were as follows: a diagnosis of epilepsy, epileptogenic lesion on imaging, or a normal 3-T MRI. Inpatient EEGs or EEGs performed in patients with acute cerebral lesions were excluded. Age- and sex-matched controls presenting with other epileptiform EEG abnormalities were selected, and similar selection criteria were applied. Results: Forty-one patients with PDs and 82 controls were selected. There were no significant differences between the cases and controls in the rates of epilepsy decompensation at the time of EEG collection or drug refractoriness. Stroke, hippocampal sclerosis, and malformations of cortical development were the most frequent etiologies, without significant differences between the groups. Conclusions: By performing a case–control study, the authors have shown that PDs are not a marker of epilepsy decompensation and drug refractoriness and that the finding of PDs is not suggestive of particular epilepsy etiologies, when compared with other epileptiform abnormalities. Abstract : Supplemental Digital Content is Available in the Text.